A mídia e a construção da identidade: análise do personagem Luca através dos gibis da Turma da Mônica - SOUSA, Vanessa Nogueira Maia de (2014)
This present work piece brings the theme of media and its relationship in the construction of identity from the consumer. The character analyzed is Luca – a disabled boy, that’s in a wheelchair - in the comic Turma da Mônica. Analyzing each appearance made by the character in the stories, for the realization of this study, the comics in Turma da Mônica are used. The objective of this research is to verify in what form is this disabled character conducted and the impact of including a disabled character in comics. The choice of the comics by Mauricio de Sousa is due to it’s brand , already known in the market and recognized by many generations, and the choice of this specific character is due to its approach, fashionable in the current scenario. Luca’s character is a disabled boy in a wheelchair, but still a happy boy, active by practicing sports, and is part of Turma da Mônica. The purpose of this project is to establish a connection of cultural studies and contribute it to studies of media and identity construction from the glance of another , being "different " , bringing this dissertation to represent the universe of a disabled.